Developing and managing requests for proposals in the public sector - Bauccio-Teschlog, Theresa; Carney, Dennis; Foster, Joyce D.; King, Ronald (Procurement officer); Weber, Christine (New York, NY : Routledge, 2021)
"American state and local governments spend roughly $3.5 trillion dollars annually fulfilling the community and governmental needs of public procurement. As governments continue to rely on the support of private sector resources and subject matter experts, mastering RFP solicitations is a critical skill required of every public procurement professional. Designed to provide a strategic overview of the skills and traits necessary to fulfill the procurement function against best value policy, this book thoroughly examines the foundational knowledge and skills needed by those who choose competitive negotiations as the best and most appropriate form for a given solicitation. Developing and Managing Requests for Proposals in the Public Sector explores the complex and ever-changing process of competitive negotiations by providing hands-on guidance for practitioners to successfully achieve the best value for their entity, as well for the taxpayer. While rules, ordinances, policies, practices, and procedures vary among entities, the book breaks down the basic steps involved in the competitive negotiation process, providing best practice guidance for public procurement professionals to help them navigate the formidable and exacting process successfully, fairly, and with transparency. This book is required reading for every public procurement professional, and will be recommended reading for all public procurement courses and certificate programs"--
"Previous edition: Developing and managing requests for proposals in the public sector / Khi V. Thai. c2007."
OCLC-licensed vendor bibliographic record.
Keywords: Government purchasing; Contracts; Negotiation; Evaluation; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Government / General